The Influence Of (Pmt-P) On The Nutritional Status Of Children In Working Area Of The Gunungkencana Community Health Center In 2022 - Ida Parida; Wintarsih . (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2023)
The purpose of this study was to determine the effect of (PMT-P) on the nutritional status of children under five in the working area of ??the Gunungkencana Health Center in 2022. The method used in the study was quassy experimental with a pre post test without control design and the research was carried out in November 2022. The population used was were toddlers with malnutrition, namely (BB/TB <-2 SD) in the Working Area of ??the Gunungkencana Health Center, totaling 45 with a sample technique using simple random sampling. As for the results of this study, it was found that in the first month the baby experienced an increase in nutritional status of 11.1% and in the second month there was a fairly good increase, namely 17.8%, as well as in the third month, the nutritional status increased, namely 28.9%. This is a very good thing with statistical tests that there is an effect of giving PMT-P on the nutritional status of toddlers who have less (p = 0.000).